PENGARUH INOVASI PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TOYOTA ALL NEW AVANZA ( STUDI PADA PELANGGAN DI DEALER AUTO 2000 A.YANI) - KHARISMA, FRESHA (Jurnal Ilmu Manajemen (JIM), 2017)
Product innovation and price perceived on consumers aims to increase car purchase, this study aims to analyze the effect of product and price innovation on purchasing decisions. Sample used in this research is 150 customers of toyota car all new avanza at dealer Auto A.yani Surabaya. Analytical techniques in this study using multiple linear regression using SPSS program version 18.0.hasil this shows that product innovation gives a partial significant influence on the purchase decision of Toyota toyota car customers in Auto Ayani dealer Surabaya and the variable price gives a significant influence Partial to the purchase decision of Toyota toyota all new avanza customers at Auto A.yani dealer Surabaya. Keywords: Product Innovation, Price, Purchase Decision